Cisplatin-eugenol Pt(IV) prodrugs target colon cancer stem cells: A novel strategy for enhanced anticancer efficacy - Novohradsky, Vojtech; Babu, Tomer; Kostrhunova, Hana; Plaskow, Menucha; Markova, Lenka; Acharya, Sourav; Gibson, Dan; Brabec, Viktor (Biomedicine & pharmacotherapy, 2025)
Platinum(IV) compounds possess distinct properties that set them apart from platinum(II) compounds. Often designed as prodrugs, they are reduced within cancer cells to their active platinum(II) form, enabling their cytotoxic effects. Their versatility also lies in their ability to be functionalized and conjugated with bioactive molecules to enhance cancer cell targeting. This report introduces new prodrugs that combine antitumor cisplatin with axially coordinated eugenol, leveraging their synergistic action to target cancer stem cells. A third bioactive ligand, 4-phenylbutyrate or octanoate, was added to further enhance biological activity, creating 'triple action' prodrugs. These new platinum(IV) prodrugs offer a novel approach to cancer therapy by improving targeting, increasing efficacy, overcoming drug resistance, and reducing tumor invasiveness while sparing healthy tissue.
Keywords: Cisplatin; lidé; prekurzory léčiv; Drug Synergism; Cell Line, Tumor; Prodrugs; Antineoplastic Agents; Neoplastic Stem Cells; eugenol; Colonic Neoplasms; protinádorové látky; Eugenol; Humans; cisplatina; synergismus léků; zvířata; nádorové kmenové buňky; Animals; nádorové buněčné linie; nádory tračníku